Gas-liquid Chromatography Analysis of Citronella Oil (Java.) - Sood, V. K. (Indian Forester, 1974)
Cymbopogon winterlanus grass cultivated in Dehra Dun has been found to contain an oil in 1.45 to 1.5 per cent. Gas-liquld chromatography analysis of the oil have shown the presence of citronellal (34.48%), citral A (4.1%), citral B (2.87%), citronellol (20.17%) and geraniol (29.08%).